Pengembangan Kewirausahaan Berbasis Pesantren: Studi Kasus Pondok Pesantren Sunan Drajat dalam Meningkatkan Kemandirian Santri dan Pertumbuhan Ekonomi Lokal - Biyati Ahwarumi; Akhmad Sirojudin Munir (Universitas Djuanda Bogor, 2026)
This study aims to analyze the implementation of the entrepreneurship program at Sunan Drajat Islamic Boarding School and its impact on enhancing students’ economic independence and local economic growth. Using a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the pesantren’s entrepreneurship program—covering service, industrial, retail, and technology sectors—has successfully improved students’ technical, managerial, and digital skills. The integration of entrepreneurship education with Islamic values also strengthens students’ ethical behavior and spiritual character in business practices. Moreover, pesantren business units contribute significantly to the local economy through job creation, collaboration with micro, small, and medium enterprises (MSMEs), and the strengthening of community-based value chains. However, several challenges remain, including limited capital, managerial literacy, and digital infrastructure. The study highlights the importance of strengthening external networks, alumni support, and digital transformation as key strategies for sustaining pesantren-based entrepreneurship. These findings are expected to serve as a reference for policymakers and pesantren administrators in developing sustainable Islamic value-based economic empowerment models.